Computational fluid dynamics investigation of heat-exchangers for various air-cooling systems in poultry houses - Trokhaniak, V.I.; Rogovskii, I.L.; Titova, L.L.; Luzan, P.H.; Popyk, P.S.; Bannyi, O.O. (KSU publ., 2020)
The increase in the productivity of poultry plants is connected with the necessity to create the optimal controlled environment in poultry houses. This problem is of prime importance due to the decrease of poultry plant productivity caused by the imperfection of the existing controlled environment systems. The paper presents the improved environment control system in a poultry house. The processes of heat- and mass-exchange in the developed heat-exchangers for various ventilation systems have been investigated. Computational Fluid Dynamics analysis of the heat-exchangers of two various designs for tunnel and side ventilation systems has been carried out. The fields of velocities, temperatures and pressures in the channels under study have been obtained. The conditions of a hydrodynamic flow in the channels have been analyzed. The intensity of heattransfer between a hot heat carrier and a cold one through their separating wall has been estimated. The most efficient heat-exchanging apparatus has been determined and the application potential of such a design has been substantiated. The aim of the research is the development and numerical modelling of a shell-and-tube heat-exchanger of a new design as an element of environment control system used in various types of ventilations systems in summer seasons.
Keywords: Heat-exchanger; Computational Fluid Dynamics; poultry house; tunnel ventilation system; side ventilation system